Indirect tax reform in Ireland: a comment - O'Hagan, John (Economic & Social Studies, 1989)
This paper essentially applies Irish data to the model developed by Ahmad and Stern. It poses three interesting questions. (i) Can we find a tax change which will. increase welfare, holding total revenue constant? (ii) What distributional value judgement is implicit in the belief that the present structure of indirect taxes is optimal? This is the inverse optimum problem. (iii) How can we maximise an increase in revenue subject to no person being made worse-off? The analysis of the first of these issues provides the core of the paper. Besides, the answers to questions (ii) and (iii) partly follow from that to question (i).
Keywords: Indirect taxation; Tax reform; Ireland